RIPE 30th anniversary special feature: looking back and looking forward in IPE. Issue 1 (2nd January 2023) - Bair, Jennifer; Elias, Juanita; Gabor, Daniela; Germain, Randall; Hozić, Aida A.; Johnston, Alison; Katada, Saori N.; Rethel, Lena; Young, Kevin L.
Abstract: The field of International Political Economy (IPE) has changed considerably since the inception of the Review of International Political Economy ( RIPE ). This 30th anniversary editorial reflects on how these changes have impacted the journal's publications over the past ten years. Some trends are promising. RIPE has become more gender inclusive, as the share of women authors in submissions and publications has risen. RIPE has also resisted the 'quantitative' focus inherent within other political science/international relations journals, continuing to publish articles that demonstrate diverse qualitative methodologies (particularly case studies). Some trends are less encouraging. RIPE has struggled to move beyond its Anglo-American base, resulting in a paucity of published authors from institutions within the Global South, and limited articles that exclusively focus on IPE phenomena in Africa, the Middle East and Latin America (although Global South countries feature more heavily within trans-regional studies published by the journal, and have similar levels of coverage as the Global North). We conclude by introducing the RIPE 30 th Anniversary Special Feature, a series of contributions by early career and emerging researchers reflecting on the history and future directions of the field of IPE. In commemorating RIPE 's 30 th anniversary by opening - and continuing to open – its pages to new authors we seek to continue a long tradition and reaffirm the journal's commitment to heterodoxy.